Strategi Guru dalam Pencegahan Perilaku Bullying melalui Pendidikan Kesehatan Diri di Sekolah Dasar - Nanda Latifa Ritonga; Mawar Sari; Nuriadani Harahap; Ilpa Khoiri; Darnia Darnia; Auliya Husna Hasbuan; Delfita Sari Ritonga; Siska Amelia; Muhammad Safri (Mutiara Pendidikan dan Olahraga, 2026)
Self-health education plays a crucial role in shaping the healthy habits, character, and behavior of elementary school students. This learning emphasizes not only physical hygiene but also the development of social and emotional skills that can prevent negative behaviors such as bullying. This study aims to examine teachers' strategies in implementing self-health education as an effort to prevent bullying behavior in elementary schools. The method used was a literature review by analyzing various relevant scientific sources from 2020–2025. The results of the study indicate that teachers' strategies in implementing self-health education include three main approaches: habituating clean and healthy living behaviors, integrating health values ​​into learning, and fostering social-emotional development through reflective activities in the classroom. These three strategies are effective in fostering students' awareness, discipline, responsibility, and empathy towards their peers. Self-health education also contributes to creating a safe, healthy, and respectful learning environment. Thus, self-health education can be used as a preventive strategy to prevent bullying in elementary schools. Teachers act as role models and facilitators who ensure the values ​​of health, empathy, and social responsibility are integrated into teaching and learning activities.